O estado desenvolvimentista no Brasil: Perspectivas históricas e comparadas - Ben Ross Schneider (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The historical success of the Asian developmental States and the partial success of developmental States in Latin America suggest numerous common requisites for an efficient State intervention, including a weberian bureaucracy, the monitoring of project implementation and reciprocity (subsidies in exchange of performance), and collaborative relations between government and private companies. Even though Brazil wasn't able to develop a high technology manufacture and exportation industry - sector that responded for continued growth in East Asia - the Brazilian developmental State had an important number of successes, often neglected, especially in steel, cars, mining, ethanol and aircrafts. Brazil was less successful in the promotion of information technology, nuclear energy and in the reduction of social and regional inequalities. Moreover, some isolated initiatives of states' governments were also efficient in the promotion of some local industrial and agricultural sectors. In contrast with Asia, Brazilian state-owned enterprises played a central role, effectively internalizing monitoring and reciprocity procedures, and ignoring the cooperation between government and private companies (which was, generally, more rare in Brazil).
Keywords: L52; O25; O40; Z18; 330; developmentalism; state-owned enterprises; public policies